2021
DOI: 10.1055/s-0041-1731393
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Socioeconomic Factors in Children with Neurofibromatosis Type 1

Abstract: The aim of this study is to analyze whether children with familial and sporadic neurofibromatosis type 1 (NF1) differ in psychosocial and socioeconomic aspects such as developmental delay as well as in comorbidities. Medical records of 250 children with NF1 at a median age of 10.6 years (range = 2–20 years at time of data collection) were retrospectively reviewed. Specifically, psychosocial and socioeconomic factors from 88 children with a family history for NF1 and 162 sporadic cases were compared. Comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Regarding disease visibility, limited existing studies have shown that greater perceived disease visibility was associated with more socioemotional problems such as depression, psychological stress [ 36 ], and negative emotions [ 35 ]. For NF1 inheritability, a few cross-sectional studies showed no difference in socioemotional functions between the familial and sporadic forms of NF1 [ 33 , 37 , 38 ]. However, it is still worthwhile to explore whether NF1 heritability may relate to changes in socioemotional functioning across time, as a prior study found that NF1 heritability was related to change (despite not initial levels) in some cognitive functions (e.g., working memory, attention, reading) over time [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding disease visibility, limited existing studies have shown that greater perceived disease visibility was associated with more socioemotional problems such as depression, psychological stress [ 36 ], and negative emotions [ 35 ]. For NF1 inheritability, a few cross-sectional studies showed no difference in socioemotional functions between the familial and sporadic forms of NF1 [ 33 , 37 , 38 ]. However, it is still worthwhile to explore whether NF1 heritability may relate to changes in socioemotional functioning across time, as a prior study found that NF1 heritability was related to change (despite not initial levels) in some cognitive functions (e.g., working memory, attention, reading) over time [ 39 ].…”
Section: Introductionmentioning
confidence: 99%